Extramedullary Plasmacytoma: A Rare Entity - Mendieta, Pastor Joaquín Ortiz; Tolentino, Luciano Henrique Lenz; Centeno, Deborah Marques; Guacho, John Alexander Lata; Felipe, Leika Miyahara; Maluf-Filho, Fauze (Journal of Digestive Endoscopy, 2023)
Extramedullary plasmacytoma is an immunoproliferative disease of mature B cell that produces immunoglobulins by clonal expansion. Plasma cell neoplasms are responsible for less than 0.1% of all pancreatic masses, they can be primary or secondary to multiple myeloma (MM). We present the case of a 56-year-old man with extramedullary solitary plasmacytoma located in the pancreas, presented with abdominal pain and jaundice. Imaging characteristics are similar to those of other pancreatic diseases, and the diagnosis is confirmed by immunohistochemistry due to the presence of a homogeneous infiltrate of monoclonal plasma cells, which typically express CD38 and CD 138 markers and the presence of kappa/lambda light chains.
Keywords: plasmacytoma; positron emission-tomography computed tomography; endosonography; endoscopic ultrasound-guided fine needle aspiration; immunohistochemistry